Peripheral blood CD34+ cells as a novel and noninvasive early marker of first trimester miscarriage: results from a case-control analysis. (17th January 2018) - Giordano, Domenico; Loddo, Saverio; Laganà, Antonio Simone; Coppolino, Giuseppe; Zoccali, Giuseppe; Di Benedetto, Antonino; Santamaria, Angelo; Buemi, Michele; D'Anna, Rosario
Abstract: Purpose: To evaluate the levels of peripheral blood CD34 +  cells in women who subsequently had a spontaneous miscarriage (SM). Materials and methods: We enrolled 11 women who had SM, matching them for age, BMI and gestational age with 33 healthy pregnancies (controls). From a blood sample at 9th–11th weeks of pregnancy, we evaluated PAPP-A, free β-hCG, T (suppressor and helper), NK, B, CD34 +  cells. Results: In peripheral blood of women who had SM, PAPP-A and CD34 +  cells were significantly lower ( p  < 0.001) compared to control group. Conclusions: CD34 +  cell low level in peripheral blood is associated with increased risk of SM.